2006
DOI: 10.1128/iai.74.1.192-201.2006
|View full text |Cite
|
Sign up to set email alerts
|

Enterocyte Cytoskeleton Changes Are Crucial for Enhanced Translocation of NonpathogenicEscherichia coliacross Metabolically Stressed Gut Epithelia

Abstract: Substantial data implicate the commensal flora as triggers for the initiation of enteric inflammation or inflammatory disease relapse. We have shown that enteric epithelia under metabolic stress respond to nonpathogenic bacteria by increases in epithelial paracellular permeability and bacterial translocation. Here we assessed the structural basis of these findings. Confluent filter-grown monolayers of the human colonic T84 epithelial cell line were treated with 0.1 mM dinitrophenol (which uncouples oxidative p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
41
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 54 publications
(42 citation statements)
references
References 53 publications
(66 reference statements)
1
41
0
Order By: Relevance
“…Dissecting the mechanism of control of epithelial barrier function, the present study adds to a body of data illustrating that paracellular and transcellular permeability are differentially regulated. Indeed, in our earlier investigations we showed that epithelia under metabolic stress have increased internalization of noninvasive E. coli (28) and that inhibitors of endocytosis and microtubule activity significantly reduced bacterial translocation across T84 cell monolayers (27). We did not specifically address the route of bacterial transcytosis in the present study.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Dissecting the mechanism of control of epithelial barrier function, the present study adds to a body of data illustrating that paracellular and transcellular permeability are differentially regulated. Indeed, in our earlier investigations we showed that epithelia under metabolic stress have increased internalization of noninvasive E. coli (28) and that inhibitors of endocytosis and microtubule activity significantly reduced bacterial translocation across T84 cell monolayers (27). We did not specifically address the route of bacterial transcytosis in the present study.…”
Section: Discussionmentioning
confidence: 80%
“…Support for this hypothesis comes from analyses of kidney-derived epithelia showing that ATP depletion affects the arrangement of tight junction proteins with a consequent increase in paracellular permeability (2, 5). Our analyses revealed that uncoupling oxidative phosphorylation (i.e., inducing metabolic stress) in epithelial monolayers by treatment with dinitrophenol (DNP) in the presence of viable, noninvasive, nonpathogenic Escherichia coli (E. coli) (strain HB101) resulted in increased paracellular and transcellular permeability (27,28).With the emergence of the concept of immunophysiology, it is clear that the function of the intestinal epithelium is affected by many immune cell types (30). The macrophage produces a plethora of messengers, including tumor necrosis factor (TNF)-␣.…”
mentioning
confidence: 99%
“…In accordance with these findings, using the MTT assay as a marker of mitochondrial activity, we found a slight reduction in mitochondrial function in T84 epithelia treated with indomethacin. Previous data show that metabolic stress induced by treatment of T84 cells with DNP is associated with reduced mitochondrial activity, which correlated with reduced expression of tight junction proteins (24,30), and increased internalization and translocation of E. coli (31). Given the energy dependence of tight junction form and function and endocytotic processes (i.e., paracellular and transcellular permeability), reduced mitochondrial function would result in reduced ATP synthesis, thus contributing to the indomethacininduced epithelial barrier defect.…”
Section: Discussionmentioning
confidence: 99%
“…E. coli (strain HB101) was grown and cultured overnight in an orbital shaker in Luria-Bertani (LB) broth at 37°C and added to the apical surface of confluent monolayers at a final concentration of 10 6 colony-forming units (cfu)/ml (23,30,31,41). A putative toxic effect of all drugs on the E. coli was evaluated in 24-h bacterial growth curves, with optical density and agar plate colony growth used to evaluate bacterial cell numbers.…”
Section: Chemicals and Bacteriamentioning
confidence: 99%
“…Given the cell biologic requirements for VgrG-1 translocation, initiation of inflammation could occur after transcytosis by a variety of several cell types, including as dendritic cells, Peyer's patch M cells (39), or even by epithelial cells (40). Although it is not clear how cross-linked actin in host cells could contribute to an inflammatory response, many cellular functions could be perturbed, and intracellular surveillance pathways could be activated.…”
Section: Discussionmentioning
confidence: 99%